2011
DOI: 10.1021/ja111201c
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Sialic Acid Residues Illuminated by Live Animal Imaging Using Phosphorylcholine Self-Assembled Monolayer-Coated Quantum Dots

Abstract: Glycans are expected to be one of the potential signal molecules for controlling drug targeting/delivery or long-term circulation of biopharmaceuticals. However, the effect of the carbohydrates of artificially glycosylated derivatives on in vivo dynamic distribution profiles after intravenous injection of model animals remains unclear due to the lack of standardized methodology and a suitable platform. We report herein an efficient and versatile method for the preparation of multifunctional quantum dots (QDs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 90 publications
1
88
0
Order By: Relevance
“…To amplify the low affinity between simple oligosaccharides and HA, glycan-modified high performance quantum dots (Glyco-PC-QDs) (Ohyanagi et al, 2011) that can be used for live animal imaging by near-infrared fluorescence photometry due to the non-fouling nature of QDs coated by phosphorylcholine self-assembled monolayers were employed. Although colorful Glyco-PC-QDs have proved to become highly sensitive fluorescent probes for direct imaging of living cells and animals by employing common fluorescence microscopic devices (Ohyanagi et al, 2011), no examples have indicated the feasibility of these ligand-conjugated QDs in quantitative analysis aiming for high-throughput screening toward drug discovery research.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To amplify the low affinity between simple oligosaccharides and HA, glycan-modified high performance quantum dots (Glyco-PC-QDs) (Ohyanagi et al, 2011) that can be used for live animal imaging by near-infrared fluorescence photometry due to the non-fouling nature of QDs coated by phosphorylcholine self-assembled monolayers were employed. Although colorful Glyco-PC-QDs have proved to become highly sensitive fluorescent probes for direct imaging of living cells and animals by employing common fluorescence microscopic devices (Ohyanagi et al, 2011), no examples have indicated the feasibility of these ligand-conjugated QDs in quantitative analysis aiming for high-throughput screening toward drug discovery research.…”
Section: Discussionmentioning
confidence: 99%
“…Egg yolk sialylated glycopeptide (A2 glycopeptide) was purchased from TCI (Tokyo, Japan). 11-Mercaptoundecylphosphorylcholine (PC-SH) and 11,11'-dithio bis [undec-11-yl 12-(aminooxyacetyl) amino hexa (ethyleneglycol) ] (ao-SH) were synthesized by the procedures reported previously (Holmlin RE et al, 2001;Nagahori et al, 2009;Ohyanagi et al, 2011). The ao-PC-QDs were prepared from the above Qdot 545 ITK, trioctylphosphine oxide (TOPO)-coated QDs (100 L of 1 M solution, 5.8 nm, CdSe/ZnS, λ em = 545 nm), by a general protocol for coating with ao-SH (50%) and PC-SH (50%).…”
Section: Reagents and The Preparation Of A2-pc-qdsmentioning
confidence: 99%
See 3 more Smart Citations